Endoparasitic infections in dogs from rural areas in the Lobos District, Buenos Aires province, Argentina - Dopchiz, Marcela Cecilia (2013)
Dogs are definite hosts for several zoonotic helminthes and protozoan. Rural areas from the Lobos District in the northeast of Buenos Aires province, Argentina, are mainly used for livestock activity, increasing in this way the number of dogs on farms as well as the human risk of parasitic infections. The aims of this research were to evaluate the endoparasitic infections in dogs from farms in the Lobos District and analyze their zoonotic importance as well as several risk practices and habits of the rural population. Forty-two dog fecal samples obtained in 21 farms were analyzed through coproparasitological methods and coproantigen tests, which resulted in an overall parasite prevalence of 69.05% and 80.95% of the parasitized farms. The most frequent parasites were Trichuris vulpis and Eucoleus aerophila (26.19%), Echinococcus granulosus (19.05%), Uncinaria stenocephala and coccids (14.29%). The analysis of epidemiological files showed several habits of the rural population considered as risk factors associated with the presence of fecal samples parasitized and the presence of E. granulosus on the farms. It is clear that people involved with the farms studied were exposed to several helminthes that could cause serious diseases like cystic echinococcosis, which can become an important public health issue and affect the economy worldwide